Fenomena Rasionalisasi Anggaran Pilkada yang Telah Disepakati: Studi Kasus di Kabupaten Ogan Komering Ulu Timur dan Kota Tidore Kepulauan - Faqih Mujahid; Susilo Harjono (Badan Pengawas Pemilihan Umum, 2020)
The budget is one aspect that determines the quality of the implementation of regional head elections (Pilkada). The budget problem that arose in the 2020 Pilkada Concurrent was the rationalization carried out by the DPRD on the Pilkada budget which was contained in the Regional Grant Agreement Text (NPHD) even though the NPHD was signed by the Regional Head and Pilkada Organizer (KPU and Bawaslu) as evidence of the budget allocation agreement for the activities of organizing and supervising the Pilkada. Examples of this rationalization practice occurred in 2 (two) regions, namely Ogan Komering Ulu Timur District, South Sumatra Province, and Tidore Islands City, North Maluku Province. There are 2 (two) factors that give rise to the rationalization problem. First, poor communication between the elements of Pilkada organizers (KPU and Bawaslu) together with the Government and the DPRD, which led to a deadlock and made the Central Government have to step in to resolve it. Second, the classic problems experienced by Indonesia in matters of legal governance that are out of sync (disharmony between regulations) have an impact on the quality of Pilkada budget management. Several things that affect the quality of Pilkada budget management include: First, the practice of assigning staff in charge of the Pilkada budget both at the KPU and Bawaslu has not fulfilled the principle of